Enhanced resonance and bandwidth performance of triband antenna through bending effect - Mohd Nor Azami, Mohd Adzimnuddin; Abd Aziz, Mohamad Zoinol Abidin; Ja'afar, Abd Shukur (2023)
A triband antenna that has difference position of monopole arm is studied for wireless communication. The study of the bending effect of the monopole arm is discussed briefly in this paper. The simulation of the triband antenna can generate the frequency at 2.56 GHz, 3.51 GHz and 4.51 GHz. The measurement of gain of the antenna is 3.21 dB, 0.01 dB and 0.80 dB, respectively.